PENGARUH PROFITABILITAS DAN AUDIT TENURE TERHADAP AUDIT REPORT LAG - Kurnia, Raisa Nur; Uzliawati, Lia; Muttaqin, Galih Fajar (LPPM Universitas Bina Bangsa, 2023)
The research was conducted on infrastructure sector companies listed on the Indonesia Stock Exchange in 2017-2021. This study aims to determine the effect of profitability and audit tenure on audit report lag. The method in this research is quantitative research with multiple linear regression. The sampling technique used is purposive sampling method. Based on the results of the study, (1) Profitability has a positive effect on audit report lag. (2) Audit tenure has no significant effect on audit report lag